N-Nonyloxypentyl-l-Deoxynojirimycin Inhibits Growth, Biofilm Formation and Virulence Factors Expression of Staphylococcus aureus - Eliana De Gregorio; Anna Esposito; Adriana Vollaro; Maria De Fenza; Daniele D'Alonzo; Antonella Migliaccio; Vita Dora Iula; Raffaele Zarrilli; Annalisa Guaragna (MDPI AG, 2020)
Staphylococcus aureus is one of the major causes of hospital- and community-associated bacterial infections throughout the world, which are difficult to treat due to the rising number of drug-resistant strains. New molecules displaying potent activity against this bacterium are urgently needed. In this study, d- and l-deoxynojirimycin (DNJ) and a small library of their N-alkyl derivatives were screened against S. aureus ATCC 29213, with the aim to identify novel candidates with inhibitory potential. Among them, N-nonyloxypentyl-l-DNJ (l-NPDNJ) proved to be the most active compound against S. aureus ATCC 29213 and its clinical isolates, with the minimum inhibitory concentration (MIC) value of 128 μg/mL. l-NPDNJ also displayed an additive effect with gentamicin and oxacillin against the gentamicin- and methicillin-resistant S. aureus isolate 00717. Sub-MIC values of l-NPDNJ affected S. aureus biofilm development in a dose-dependent manner, inducing a strong reduction in biofilm biomass. Moreover, real-time reverse transcriptase PCR analysis revealed that l-NPDNJ effectively inhibited at sub-MIC values the transcription of the spa, hla, hlb and sea virulence genes, as well as the agrA and saeR response regulator genes.